Analisis Rantai Pasok dan Nilai Tambah Agroindustri Gula Merah Aren di Desa Rambah Tengah Barat Kecamatan Rambah Kabupaten Rokan Hulu - Muhammad Fajar Sidik; Farida Hanum Hamzah; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Palm plants grow evenly in Indonesia, one of which is in Rokan Hulu Regency, Riau. Especially in Rambah District which has the largest area and the highest palm production. Palm sap is widely used for palm sugar processing, but the agro-industry is experiencing difficulties in information and technology so that it does not run effectively and efficiently which results in a lack of income. The purpose of this research is to identify the supply chain to increase the added value of palm sugar agroindustry. This research was conducted by observation and field interviews with descriptive qualitative and quantitative methods. Qualitative descriptive analysis was performed using SWOT (Strengths, Weaknesses, Opportunities, and Threats) and AHP (Analytical Hierarchy Process). Quantitative descriptive analysis using the Hayami method. The data collection method was done by using purposive sampling. The results showed a supply chain pattern, namely: farmer-collector-retailer-end-consumer. The calculation of added value obtained by farmers is Rp. 2,400 with a ratio of 54.55% and collectors of Rp. 4,600 with a ratio of 15.54%. The result of AHP's analysis is to expand the marketing network and partnerships. Keywords: sugar palm, supply chain, added value, SWOT, AHP